RISK ASSESSMENT PADA PEKERJAAN MENEBANG KAYU DI HUTAN PRODUKSI (STUDI KASUS PADA PENGOPERASIAN CHAINSAW PERUM PERHUTANI KPH MADIUN) - Raditya Angga Pradipta (The Indonesian Journal of Occupational Safety and Health, 2016)
Logging the forest production is a high risk work. The condition of the forest acreage is difficult, the imbalance between the tools used by condition of the field and the skills of workers can lead to accidents. One of supporting job in the process of logging the forest production is the operation of the chainsaw that has hazards and risks which must be controlled. The main objective of this research was to risk assessment in the operational of the chainsaw in the work to cutting down trees in Perhutani KPH Madiun. This research was an observational research that conducted using cross sectional design and descriptive analysis. Data were used primary data based on interviews, observations and secondary data collected from the company. This research performed based on work activities of operating chainsaw. The result showed that based on idetification of hazards in activities of operating chainsaw in cutting trees, there were18 hazards Risk assessment showed that from 18 pure risks, there were 4 low risks,7 medium risks and 7 high risks. The conclusion from this research is the risk most dominant obtained from the risk assessment is high risk and risks while each one had the amount of 7 danger or 39 % of all the potential here hazards, to at a job should not be continued, work that needs to be set repeated or attempts to control at work to reduce the risk. Control must be reviewed for conformity before work began.Keywords: cut timber, identification hazards, risk assessment